Making Christianity manly again: Mark Driscoll, Mars Hill Church, and American evangelicalism - McKinney, Jennifer (Oxford University Press, 2023)
"Bewildered by the 81 percent of white evangelicals voting for Donald Trump in the 2016 Presidential election, post-election commentators asked, "How could 'family values' conservatives vote for a man flouting every value they espoused?" or more colorfully, "How could so many conservative evangelicals have voted for a thrice-married casino mogul who has bragged about assaulting women and rarely goes to church?" These questions were valid, because evangelical support for political candidates had traditionally hinged on a candidate's moral behavior. In a 2011 Public Religion Research Institute (PRRI) survey, for example, 30 percent of white evangelical Protestants agreed with the statement, "Because things have gotten so far off track in this country, we need a leader who is willing to break some rules if that's what it takes to set things right." By 2016, the percentage of white evangelical Protestants agreeing with that statement had more than doubled, increasing to 72 percent. In fact, breaking the rules seemed to galvanize Trump's appeal. The more raucous Trump and his campaign became, the more white evangelicals rallied to him, ultimately delivering him a victory"--